The Effect of Two Stay Two Stray Strategy on Students’ Reading Comprehension of Narrative Text - A.Muliyana A.Azis; Sultan Baa; Maemuna Muhayyang (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
This research was aimed to determine whether the use of Two Stay Two Stray (TSTS) strategy can improve students' reading comprehension of narrative texts. The researcher applied an experimental design. The population of this research was the eight-year students of SMP Negeri 1 Liliriaja with a sample of 56 students using a purposive sampling technique, and two classes were taken as samples; they were VIII A as the experimental class and VIII B as the control class. The researcher used a reading test as instrument.  The results showed that by using the Two Stay Two Stray (TSTS) strategy on students' reading comprehension of narrative texts was improved. This can be seen from the students' post-test scores which were higher than the pre-test scores. The mean score of pre-test in experimental class VIII A was 48.57 and the post-test was 86.79, meanwhile the mean score of pre-test in  control class VIII B was 54.64 and the post-test was 65.36. In addition, as evidenced by an independent test, the t-count value of 7.304 was greater than the t-table value of 1.67. So it can be concluded that the use of Two Stay Two Stray strategy is effective on reading comprehension of narrative texts at the eight-year students of SMP Negeri 1 Liliriaja.Keywords: Two Stay Two Stray, Reading Comprehension, Narrative Text.